DESAIN KESIAPSIAGAAN TANGGAP DARURAT KEBAKARAN DI PASAR TRADISIONAL BOJA KABUPATEN KENDAL 2021 - Adhiatma, Pramudya Fahry; Kurniawan, Bina; Ekawati, Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Boja Market is the main market in Boja District, Kendal, Central Java. Products from agriculture (fruits and vegetables) as well as industrial goods (clothing and electronics) can be sold in this market. Boja Market experienced a fire accident in 2007. As a result, traders suffered losses in the form of burned goods and trading activities in the market were hampered because traders lost their places to trade. Therefore, it is necessary to do fire prevention efforts to prevent fires from occurring. The purpose of this study was to design fire prevention efforts in the Boja Traditional Market, Kendal Regency based on the standard. This research is qualitative descriptive research. The research uses in-depth interviews and field observations, then the existing data is compared with standards for further analysis and design processes. The variable in this study is fire prevention efforts, includes: fire management and fire fighting facilities. The results of the study carried out a comparative analysis with applicable regulatory standards. The proposed design for supporting fire prevention efforts include: organizational structure for fire prevention, standard operating procedures for fire prevention and design of fire facilities layout plans. Traditional Boja Market, Kendal Regency, has carried out fire prevention efforts but has not been maximized so that researchers provide suggestions in the form of designs that are expected to be applied in the market.